2010
DOI: 10.1148/radiol.10091140
|View full text |Cite
|
Sign up to set email alerts
|

Middle Ear Cholesteatoma: Non–Echo-planar Diffusion-weighted MR Imaging versus Delayed Gadolinium-enhanced T1-weighted MR Imaging—Value in Detection

Abstract: Purpose:To retrospectively compare non-echo-planar (non-EP) diffusion-weighted (DW) imaging, delayed gadoliniumenhanced T1-weighted magnetic resonance (MR) imaging, and the combination of both techniques in the evaluation of patients with cholesteatoma. Materials and Methods:This institutional review board-approved study, for which the need to obtain informed consent was waived, included 57 patients clinically suspected of having a middle ear cholesteatoma without a history of surgery and 63 patients imaged be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
92
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 12 publications
7
92
0
9
Order By: Relevance
“…Delayed phase gadolinium enhanced T1 W imaging can be used for the diagnosis of cholesteatoma; however there are conflicting data about this method in the literature. Although some authors suggested that delayed phase post-contrast imaging is useful, others indicated that delayed phase post-contrast imaging could not provide additive information [9,16]. These conflicting results were believed to be related with the dimension of cholesteatoma [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed phase gadolinium enhanced T1 W imaging can be used for the diagnosis of cholesteatoma; however there are conflicting data about this method in the literature. Although some authors suggested that delayed phase post-contrast imaging is useful, others indicated that delayed phase post-contrast imaging could not provide additive information [9,16]. These conflicting results were believed to be related with the dimension of cholesteatoma [16].…”
Section: Discussionmentioning
confidence: 99%
“…Geometric distortion may lead to false negative or positive results by preventing the optimal evaluation of middle ear cavity and those artefacts are more prominent at 3 tesla (T) devices [2,8]. New techniques have been developed to avoid these artefacts including multi-shot echo-planar imaging (EPI), non-EPI or periodically rotated overlapping parallel lines with enhancedreconstruction (PROPELLER) techniques [2,7,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the high signal intensity is assumed to be a T2 shine-through effect or the restricted molecular diffusion of cholesteatoma. SS EPI-DWI frequently leads to artifacts, which could mask areas of restricted diffusion in a cholesteatoma and therefore SS EPI-DWI is no longer recommended [60,61]. The presently used non-EPI DWI method combines a sensitivity of 91.4 % and a positive predictive value of 97.3 % with a negative predictive value of 85 % [62].…”
Section: Diffusion-weighted Imaging (Epi-dwi Non-epi-dwi Resolve)mentioning
confidence: 99%
“…Non-EPI DWI thus can prevent unnecessary revision surgery in patients who are suspected of having recurrent or residual disease as CT cannot discriminate cholesteatoma within a soft-tissue mass or partially filled with nonspecific imaging abnormalities [62]. DWI may also replace delayed gadolinium-enhanced T1w sequences [60]. Images from non-EPI sequences or newer EPI techniques such as RESOLVE can even be fused with anatomical images (T1w and T2w) in coronal and/or axial orientation to better localize suspected lesions [63,64].…”
Section: Diffusion-weighted Imaging (Epi-dwi Non-epi-dwi Resolve)mentioning
confidence: 99%
See 1 more Smart Citation